Community isomorphism and corporate social action - Marquis, Christopher; Glynn, Mary Ann; Davis, Gerald F. (Academy of Management Review, 2007)
We present a model of how institutional pressures at the community level shape corporate social action—behaviors and practices that extend beyond immediate profit maximization goals and are intended to increase social benefits or mitigate social problems for constituencies external to the firm—within the metropolitan area where firms are headquartered. We propose that community isomorphism influences the nature and level of corporate social action within communities and conclude with theoretical implications emphasizing the community as the focal unit of analysis for understanding corporate social action.